2023
DOI: 10.1039/d2tc04961a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent hydrogels with emission enhancement and CPL-activity depending on gelation states

Abstract: Photoluminescence properties of fluorescent hydrogels are strongly influenced by the supramolecular organization of the chromophores, which make their modulation nontrivial. In this work, a series of fluorescent hydrogels with different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The authors expect that CPL can be more precisely controlled using solid-phase peptide synthesis to obtain peptides with well-defined structures. Some research groups that conducted studies on the peptide-based regulation of CPLs recently reported that they succeeded in generating CPL from achiral molecules incorporated into peptide assemblies and peptide-based assemblies [7][8][9][10][11][12][13][14][15]. These research groups used peptides of various sizes, from dipeptides to polymeric peptides, to form peptide aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The authors expect that CPL can be more precisely controlled using solid-phase peptide synthesis to obtain peptides with well-defined structures. Some research groups that conducted studies on the peptide-based regulation of CPLs recently reported that they succeeded in generating CPL from achiral molecules incorporated into peptide assemblies and peptide-based assemblies [7][8][9][10][11][12][13][14][15]. These research groups used peptides of various sizes, from dipeptides to polymeric peptides, to form peptide aggregates.…”
Section: Introductionmentioning
confidence: 99%